PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND AWARENESS PADA E-COMMERCE HIJUP - Nina Halimatu Salamah, (2021)
This research is a quantitative study that aims to determine the effect of social media marketing towards brand awareness on Hijup e-commerce. The population in this study were Muslim women who were active users of social media and who also lived or who are doing activities in he area around Jakarta. The sample size was taken as many as 70 respondents, with a non-probability sampling method with purposive sampling type. Data collection was carried out by distributing online questionnaires, which is the google form. The data analysis technique used is descriptive and inferential analysis, using a tool for testing, namely SPSS Version 26. The results of this study indicate that social media marketing has a significant effect on brand awareness by 39%.